Peningkatan Kapasitas Kelompok Tani dan Karang Taruna Desa Peron Melalui Pelatihan Pembuatan Pupuk Organik Cair Dari Limbah Kulit Kopi - Agnaf Naufal, Muhammad; Dias Nanda, Aurelia; Primagati, Aira; Nur Hidayat, Farid; Najwa, Rizqa; Haris, Amnan (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The community service program carried out by team PPK Ormawa Hima IPA dan Lingkungan 2025, titled “Z-agroforestrypreneur”, took place in Peron Village, Limbangan Distict, Kendal Regency. The village is known for its fertile hilly terrain and high agricultural potential, particularly Robusta coffee. To date, coffee processing in Peron Village has produced large amounts of coffee husk waste, yet the community has not been able to utilize it, and it often causes environmental pollution. This program aimed to empower farmer groups and the local youth organization (Karang Taruna) through hands-on training in producing liquid organic fertilizer (POC) from coffee husk waste. The implementation method consisted of preparation, execution, and evaluation stages, starting with coordination with relevant stakeholders, followed by POC production demonstrations, and ending with assessments of participants’ skills. The results showed a moderate increase in participants’ knowledge and skills, with an N-Gain score of 0.4081, indicating the effectiveness of the training. Participants successfully produced POC products and demonstrated readiness to produce them independently. Beyond providing an environmentally friendly waste management solution, the program also opened opportunities for added economic value and supported sustainable agriculture in Peron Village.